Association between antibody responses post-vaccination and severe COVID-19 outcomes in Scotland - Macdonald, C; Palmateer, N; McAuley, A; Lindsay, L; Hasan, T; Hameed, SS; Hall, E; Jeffrey, K; Grange, Z; Gousias, P; Mavin, S; Jarvis, L; et al. (Nature Research, 2024)
Several population-level studies have described individual clinical risk factors associated with suboptimal antibody responses following COVID-19 vaccination, but none have examined multimorbidity. Others have shown that suboptimal post-vaccination responses offer reduced protection to subsequent SARS-CoV-2 infection; however, the level of protection from COVID-19 hospitalisation/death remains unconfirmed. We use national Scottish datasets to investigate the association between multimorbidity and testing antibody-negative, examining the correlation between antibody levels and subsequent COVID-19 hospitalisation/death among double-vaccinated individuals. We found that individuals with multimorbidity ( ≥ five conditions) were more likely to test antibody-negative post-vaccination and 13.37 [6.05–29.53] times more likely to be hospitalised/die from COVID-19 than individuals without conditions. We also show a dose-dependent association between post-vaccination antibody levels and COVID-19 hospitalisation or death, with those with undetectable antibody levels at a significantly higher risk (HR 9.21 [95% CI 4.63–18.29]) of these serious outcomes compared to those with high antibody levels.